Horizontal gene transfer in bdelloid rotifers is ancient, ongoing and more frequent in species from desiccating habitats - Eyres,I; Boschetti,C; Crisp,A; Smith,TP; Fontaneto,D; Tunnacliffe,A; Barraclough,TG (BMC Biology, 2015)
Background: Although prevalent in prokaryotes, horizontal gene transfer (HGT) is rarer inmulticellular eukaryotes. Bdelloids rotifers are microscopic animals that contain a higherproportion of horizontally transferred, non-metazoan genes in their genomes than typical ofanimals. It has been hypothesized that bdelloids incorporate foreign DNA when they repairtheir chromosomes following double-strand breaks caused by desiccation. HGT might therebycontribute to species divergence and adaptation, as in prokaryotes. If so, we expect thatspecies should differ in their complement of foreign genes, rather than sharing the same set offoreign genes inherited from a common ancestor. Furthermore, there should be more foreigngenes in species that desiccate more frequently. We tested these hypotheses by surveyingHGT in four congeneric species of bdelloids from different habitats: two from permanentaquatic habitats and two from temporary aquatic habitats that desiccate regularly.Results: Transcriptomes of all four species contain many genes with a closer match to nonmetazoangenes than to metazoan genes. Whole genome sequencing of one species confirmedthe presence of these foreign genes in the genome. Nearly half of foreign genes are sharedbetween all four species and an outgroup from another family, but many hundreds are uniqueto particular species, which indicates that HGT is ongoing. Using a dated phylogeny, weestimate an average of 12.8 gains versus 2.0 losses of foreign genes per million years.Consistent with the desiccation hypothesis, the level of HGT is higher in the species thatexperience regular desiccation events than those that do not. However, HGT still contributedhundreds of foreign genes to the species from permanently aquatic habitats. Foreign geneswere mainly enzymes with various annotated functions that include catabolism of complexpolysaccharides and stress responses. We found evidence of differential loss of ancestralforeign genes previously associated with desic